PERBEDAAN PENGARUH HASIL LATIHAN PEREGANGAN STATIS DAN DINAMIS TERHADAP KELENTUKAN TOGOK MENURUT JENIS KELAMIN ANAK KELAS 3 DAN 4 SEKOLAH DASAR - Fredericus Suharjana (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2013)
This study aimed to determine: (1) The defferent in the effect of static and dynamic stretching exercise to torso’sflexibility of the student in the grade 3 and 4 of Elementary School; (2) The different of torso’s flexibility betweenboys and girls in the grade 3 and 4 of Elementary School; (3) Interaction between the effect of stretching exerciseand sex type to torso’s fexibility of student in the grade of 3 and 4 of Elementary School. The research method isexperimental, with the total population of all boys and girls in the grade 3 and 4 of all the Elementary School in theKulon Progo district are 261 School and 6.469 students. The research sample is determined by multi-stage randomsampling method, it is Ngemplak Elementary School of UPTD PAUD DIKDAS – Kalibawang with 20 boys and 20girls. Research instrument used to determine the level of child’s torso’s flexibility is a series of test which havebeen developed by the author and have been trialed before. Reliability coefficient obtained by Hoyt technique; totalreliability coefficient result are 0.719 for men and 0.700 for women. Validity coefficients obtained by the total sectiontechnique: the result for men torso’s flexibility test; r = 0.657 to the left side. As for women torso’s flexibility test: r =0.600 to the forward, r = 0.645 to the backward, r = 0.827 to the right side, r = 0.829 to the left side. All significant atthe level α = 0.05 The data analysis technique used is 2 x 2 ANOVA at significant level α = 0.05. F test results are:(1) for variable A that is static and dynamic stretching exercises obtained Fo = 45.565 Ft = 4.11 means that Ho isrejected and Ha accepted, in this case there is a significantly different effect between static and dynamic stretchingon torso’s flexibility for students in the grade 3 and 4 of Elementary Schools, (2) for variable B which is a Sex typeof men and women obtained Fo = 1.865 4.11 mean Ho is accepted and Ha is rejected, in this case there is nodifferent of torso’s flexibility between the boys and girls in the grade 3 and 4 of Elementary School, (3) for inter ABwhich is the interaction between the effect of stretching exercise and Sex type to torso’s flexibility obtained Fo =3.292 Ft = 4.11 means Ho is accepted and Ha is rejected, in this case there is no interaction between the effect ofstretching exercise and Sex type to the torso’s fexibility of the students in the grade 3 and 4 of Elementary School.Keywords: Stretching Exercise, Flexibility, Static, Dynamic, Torso.